Evaluasi Aktivitas Antidiabetes In Vivo dari Fraksi Etil Asetat dan n-Heksana Ekstrak Kulit Kayu Raru (Cotylelobium melanoxylon) pada Model Tikus Diabetes yang Diinduksi Aloksan - Rio Sinar Parsaoran Simanullang; Roy Indrianto Bangar; Astriani Natalia Br. Ginting (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Introduction: Diabetes mellitus is a chronic metabolic disease with continuously increasing global prevalence, driving the search for safer and more effective alternative therapies based on natural ingredients. Raru bark (Cotylelobium melanoxylon) has been traditionally used as an antidiabetic agent, yet scientific evidence supporting the efficacy of its specific fractions remains limited. Methods: This laboratory experimental study evaluated the antidiabetic activity of ethyl acetate and n-hexane fractions of raru bark ethanol extract in alloxan-induced male Wistar rats (n=3 per group). Extraction was performed using maceration method with 96% ethanol, followed by sequential liquid-liquid fractionation. Simplicia characterization included determination of water content, total ash content, acid-insoluble ash content, as well as water-soluble and ethanol-soluble extractive values. Phytochemical screening was conducted qualitatively, while blood glucose levels were measured periodically over 14 days and analyzed using one-way ANOVA (p<0.05). Results: Simplicia characterization met the requirements of the Indonesian Herbal Pharmacopoeia with water content of 9.99%, total ash content of 1.78%, and acid-insoluble ash content of 0.19%. Phytochemical screening confirmed the presence of alkaloids, flavonoids, saponins, and tannins. The ethyl acetate fraction demonstrated more significant blood glucose reduction (318→95 mg/dL) compared to the n-hexane fraction (312→160 mg/dL) over the 14-day observation period, with a final mean value approaching that of the positive control (80.00±11.66 mg/dL). Statistical analysis revealed significant differences among treatment groups (p<0.05). Conclusion: The ethyl acetate fraction of raru bark extract exhibited superior in vivo antidiabetic activity compared to the n-hexane fraction in alloxan-induced diabetic rat models, correlating with the content of semi-polar compounds such as flavonoids and phenolics. The ethyl acetate fraction shows potential for development as a natural-based antidiabetic agent.